Elevated serum procalcitonin early after extensive burn: influencing factors and clinical significance. Issue 6 (September 2021) - Xu, Long; Jin, Jian; Wu, Guosheng; Chen, Tiansheng; Xu, Dayuan; Zhu, Feng; Xiao, Shichu; Xia, Zhaofan; Wang, Guangyi
Highlights: Serum PCT was elevated in 50.93% of the extensive-burn cases Elevated PCT during shock seems not to be caused by infectious factors Elevated PCT correlated with burn index, APACHE-II score, and inhalation injury Elevated PCT may serve as an indicator of burn severity during early burn injury Abstract: The study was carried out to analyze the factors influencing the elevated serum procalcitonin (PCT) levels during the early phase of extensive burn, and to investigate its potential for sepsis prediction and prognosis. Clinical data of 324 patients with extensive burns treated at our department from July 2014 to December 2019 were retrospectively analyzed. Approximately half of the patients (50.93%) exhibited elevated serum PCT concentrations during the early phase, and elevated PCT levels may not be caused by infections. Early-phase PCT level was an independent risk factor for sepsis occurrence in extensive-burn patients within 60 days of injury. Burn index, degree of inhalation injury, and APACHE-II score influenced PCT level elevation during the early phase. Patient age, burn index, APACHE-II score at admission, early-phase PCT level, and sepsis occurrence were risk factors for mortality in extensive-burn patients. During the early phase, approximately 50.93% of the extensive-burn patients exhibited elevated PCT levels, which were associated with non-infectious factors. As elevated PCT level during the early phase predicted sepsis occurrence within 60 days of injury and was significantly associated with patient mortality, it might be a potential burn severity indicator during the early phase of burn injury.